Meta-Analisis Pengaruh RME terhadap Kemampuan Berpikir Kritis Siswa - Irfantoni Indrastoto; Ali Mahmudi (Mandalika Mathematics and Educations Journal, 2025)
This study aims to conduct a meta-analysis of studies evaluating the impact of the Realistic Mathematics Education (RME) approach on enhancing students' critical thinking skills. Using a meta-analytic method, this research combines data from 16 studies to calculate effect sizes, test data heterogeneity, and analyze moderator variables. The effect size is calculated using the Hedges' g formula and classified according to Cohen's criteria: small (less than 0.2), medium (0.2–0.5), and large (above 0.8). The findings show that RME has a significant positive impact, with effect sizes ranging from 0.193 to 2.737. The largest impact was found in urban areas (effect size 1.2014) compared to rural areas (effect size 0.5581). At the elementary school level, the effect size was 0.7908, and at the junior high school level, it was 0.8287. The highest effect size was recorded in the 2023–2025 period (1.1487). Based on these results, it is recommended that educators and policymakers adopt the RME approach, considering local context and student characteristics. Further research with a larger dataset will strengthen statistical validity and deepen understanding of RME implementation in various learning contexts.